RANCANG BANGUN MESIN PENGIRIS DAUN BAWANG DENGAN KAPASITAS 300 GRAM PER MENIT - Muhammad Ramadhan (Journal of Mechanical Engineering and Mechatronics, 2021)
The need for sliced scallions is relatively large, so a tool that can assist in the slicing process is more effective both in terms of energy and time spent. Based on these problems, the idea was born to design a scallion slicing machine to help the community in slicing scallions, especially food sellers who need scallions such as egg martabak sellers, and food sellers.The method used is literature study (library), field observations, and problem-solving methods in the form of design which includes pre-planning in the form of machine sketches, machine concept planning, calculations, making working drawings, procurement of materials and components, toolmaking, assembly, and testing.The output of this final project is the manufacture of a scallion slicing machine that is simple and effective by not forgetting the safety and hygiene factors so that it can support the slicing process at the scale of traders and home industries. This tool has a capacity of 300 grams per minute using a DC 775 motor and is sourced from four 18650 li-ion batteries.